(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Seen in Iraq that the volume of insurance activity in the case of a clear deterioration and a sharp decline in demand for life insurance, because of reluctance by senior members of the Iraqi society on the demand for life insurance. The study was descriptive approach in identifying and addressing variables, namely the (perception of risk need of the individual trends in personal income of the individual insurance awareness of the individual customs and traditions of communal religious belief of the individual age and sex of the individual methods promotional company competitive alternatives to the insurance service life inflation rate service life insurance) independent variables and the demand for life insurance as the dependent variable, and the purpose of achieving the objectives of the research were formulated three hypotheses were tested on a sample of persons who are not faithful to their’s (150) personnel, the researcher used form questionnaire to collect data and information needed for the study.